Cocaine-induced increases in motivation require 2-arachidonoylglycerol mobilization and CB1 receptor activation in the ventral tegmental area. (1st August 2021) - Engi, Sheila A.; Beebe, Erin J.; Ayvazian, Victoria M.; Cruz, Fabio C.; Cheer, Joseph F.; Wenzel, Jennifer M.; Zlebnik, Natalie E.
Abstract: A wide body of evidence supports an integral role for mesolimbic dopamine (DA) in motivated behavior. In brief, drugs that increase DA in mesolimbic terminal regions, like cocaine, enhance motivation, while drugs that decrease DA concentration reduce motivation. Data from our laboratory and others shows that phasic activation of mesolimbic DA requires signaling at cannabinoid type-1 (CB1) receptors in the ventral tegmental area (VTA), and systemic delivery of CB1 receptor antagonists reduces DA cell activity and attenuates motivated behaviors. Recent findings demonstrate that cocaine mobilizes the endocannabinoid 2-arachidonoylglycerol (2-AG) in the VTA to cause phasic activation of DA neurons and terminal DA release. It remains unclear, however, if cocaine-induced midbrain 2-AG signaling contributes to the motivation-enhancing effects of cocaine. To examine this, we trained male and female rats on a progressive ratio (PR) task for a food reinforcer. Each rat underwent a series of tests in which they were pretreated with cocaine alone or in combination with systemic or intra-VTA administration of the CB1 receptor antagonist rimonabant or the 2-AG synthesis inhibitor tetrahydrolipstatin (THL). Cocaine increased motivation, measured by augmented PR breakpoints, while rimonabant dose-dependently decreased motivation. Importantly, intra-VTA administration of rimonabant or THL, at doses that did not decrease breakpoints on their own, blocked systemic cocaine administration from increasing breakpoints in male and female rats. These data suggest that cocaine-induced increases in motivation require 2-AG signaling at CB1 receptors in the VTA and may provide critical insight into cannabinoid-based pharmacotherapeutic targets for the successful treatment of substance abuse. Highlights: Cocaine increases food-motivated behavior through an unknown mechanism. Systemic CB1 receptor blockade decreased cocaine-induced motivation. Antagonizing CB1 receptors in the VTA reduced cocaine-induced motivation. Blocking VTA 2-AG synthesis prevented increases in cocaine-induced motivation. Cocaine promotes motivated behavior through midbrain endocannabinoid signaling.